2014
DOI: 10.1039/c4ra11842a
|View full text |Cite
|
Sign up to set email alerts
|

A tensiometric study of magnetorheological suspensions' stability

Abstract: A thin (3-aminopropyl)triethoxysilane (3APTS) layer with a grafting density around 50 groups per nm 2 was coated onto soft magnetic carbonyl iron (CI) particles. Their physical characteristics were examined using various methods, and the results revealed that the coating layer did not affect the particles' morphology and magnetic properties while their resistance against thermal oxidation and chemical degradation was considerably improved. This study further evaluates the surface free energy of the particles u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…An evaluation of sedimentation stability of MR suspensions via tensiometry was recently proposed by Sedlacik et al 38 MR suspensions containing 10 wt% (approx. An evaluation of sedimentation stability of MR suspensions via tensiometry was recently proposed by Sedlacik et al 38 MR suspensions containing 10 wt% (approx.…”
Section: Sedimentation Stability Measurementsmentioning
confidence: 99%
“…An evaluation of sedimentation stability of MR suspensions via tensiometry was recently proposed by Sedlacik et al 38 MR suspensions containing 10 wt% (approx. An evaluation of sedimentation stability of MR suspensions via tensiometry was recently proposed by Sedlacik et al 38 MR suspensions containing 10 wt% (approx.…”
Section: Sedimentation Stability Measurementsmentioning
confidence: 99%
“…10 Here, a series of peaks correspond to zinc sulphate hydroxide tetrahydrate Zn 4 SO 4 (OH) 6 $4H 2 O (ICDD-JCPDS PDF-2 entry 01-072-130500-044-0673) and zinc sulphate hydroxide pentahydrate Zn 4 SO 4 (OH) 6 $5H 2 O (ICDD-JCPDS PDF-2 entry 01-072-130500-039-0688), which indicates the presence of a mixture of both compounds. 10 Here, a series of peaks correspond to zinc sulphate hydroxide tetrahydrate Zn 4 SO 4 (OH) 6 $4H 2 O (ICDD-JCPDS PDF-2 entry 01-072-130500-044-0673) and zinc sulphate hydroxide pentahydrate Zn 4 SO 4 (OH) 6 $5H 2 O (ICDD-JCPDS PDF-2 entry 01-072-130500-039-0688), which indicates the presence of a mixture of both compounds.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Such suspensions are usually composed of micron-sized ferromagnetic 4-6 particles with high saturation magnetization dispersed in a nonmagnetic carrier liquid. [9][10][11][12][13][14] Therefore, due to their extraordinary properties, MR suspensions have recently begun to be utilized in many industrial applications. 7,8 Generally, in the absence of an external magnetic eld, the particles are randomly dispersed in the carrier liquid and the suspensions exhibit a Newtonian-like behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the presence of guar gum enhances the thixotropy and sedimentation stability effectively. Sedlacik et al [7] employed the method of coating a thin layer of 3APTS with a grafting density of 50 groups/nm 2 , and identified improved compatibility of non-polar silicone oil with coated particles. Kumar [8] studied the characterization of honey oil-based MR fluid for the brake applications, whereas the degradation and stability of the fluid were not critically identified.…”
Section: Introductionmentioning
confidence: 99%